2006
DOI: 10.1051/0004-6361:20054255
|View full text |Cite
|
Sign up to set email alerts
|

Full polarization study of SiO masers at 86 GHz

Abstract: Aims. We study the polarization of the SiO maser emission in a representative sample of evolved stars in order to derive an estimate of the strength of the magnetic field, and thus determine the influence of this magnetic field on evolved stars. Methods. We made simultaneous spectroscopic measurements of the 4 Stokes parameters, from which we derived the circular and linear polarization levels. The observations were made with the IF polarimeter installed at the IRAM 30 m telescope. Results. A discussion of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
126
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(155 citation statements)
references
References 52 publications
(86 reference statements)
28
126
1
Order By: Relevance
“…Blackman et al (2001) argue that some remnant field anchored in the core will survive even without a convection zone, although the convective envelope may not be removed completely. The idea that magnetic fields are important ingredients shaping PNe has been supported by the detection of SiO, H 2 O, and OH maser emission in circumstellar envelopes of AGB stars pointing at milliGauss fields in these nebula (Kemball & Diamond 1997;Szymczak & Cohen 1997;Miranda et al 2001;Vlemmings et al 2002Vlemmings et al , 2005Vlemmings et al , 2006Herpin et al 2006;Sabin et al 2007;Kemball et al 2009;Gómez et al 2009;Vlemmings 2011). Moreover, using an idea of Pascoli (1985), Huggins & Manley (2005) connected the extreme filamentary structures seen in high-resolution optical images of certain PNe to magnetic fields consistent with those measured in the maser from the precursor circumstellar envelopes.…”
Section: Introductionmentioning
confidence: 91%
“…Blackman et al (2001) argue that some remnant field anchored in the core will survive even without a convection zone, although the convective envelope may not be removed completely. The idea that magnetic fields are important ingredients shaping PNe has been supported by the detection of SiO, H 2 O, and OH maser emission in circumstellar envelopes of AGB stars pointing at milliGauss fields in these nebula (Kemball & Diamond 1997;Szymczak & Cohen 1997;Miranda et al 2001;Vlemmings et al 2002Vlemmings et al , 2005Vlemmings et al , 2006Herpin et al 2006;Sabin et al 2007;Kemball et al 2009;Gómez et al 2009;Vlemmings 2011). Moreover, using an idea of Pascoli (1985), Huggins & Manley (2005) connected the extreme filamentary structures seen in high-resolution optical images of certain PNe to magnetic fields consistent with those measured in the maser from the precursor circumstellar envelopes.…”
Section: Introductionmentioning
confidence: 91%
“…they are not the source of localized magnetic fields unrelated to the global field issued from the central star. Fig.4 includes previous measurements of SiO masers (Kemball et al 2009;Herpin et al 2006), H2O masers (Vlemmings et al 2002(Vlemmings et al , 2005 and OH masers (Rudnitski et al 2010) giving us an overview of the maser and magnetic field strength distributions in evolved stars. Thus, Vlemmings (2011) summarised the results of the aforementioned studies related to the characteristics of masers in AGB stars (the behaviour is similar in PAGB stars) and noted some correlations through the different investigations in terms of strength and location of each masers.…”
Section: Prediction Of Maser Strengths In the Envelope Of U Monmentioning
confidence: 99%
“…Both single-dish and interferometric observations have revealed that silicon monoxide (SiO), water (H 2 O), hydrogen cyanide (HCN), hydroxyl (OH), and methanol (CH 3 OH), among others, can naturally generate polarized maser emission in these enviroments (e.g. Vlemmings et al 2006b;Surcis et al 2011;Fish & Reid 2007b;Herpin et al 2006;Kemball et al 2009). In particular, interferometric observations of the masers at radio wavelengths have become a useful tool for studying the magnetic field in and around SFRs and late-type stars (e.g.…”
Section: Introductionmentioning
confidence: 99%